Septicemia and Aortic Valve Endocarditis due to Erysipelothrix rhusiopathiae in a Homeless Man - Dean Campbell; Mark Cowan (Case Reports in Infectious Diseases)
We report a case of bacterial endocarditis due to Erysipelothrix rhusiopathiae in a homeless man with no animal exposure. His course was complicated by an allergic reaction to ampicillin, urinary bladder infection, respiratory failure, and acute kidney injury. He recovered completely after aortic valve replacement and a 6-week course of intravenous ceftriaxone.